Human Exposures to H5N6 Avian Influenza, England, 2018. (21st February 2019) - Thornton, Alicia C; Parry-Ford, Frances; Tessier, Elise; Oppilamany, Nisha; Zhao, Hongxin; Dunning, Jake; Pebody, Richard; Dabrera, Gavin
Abstract: The human risk following exposure to the European reassortant avian influenza A(H5N6) is unknown. We used routine data collected as part of public health follow-up to assess outcomes of individuals exposed to H5N6-infected wild birds in England. There were 19 separate incidents of confirmed H5N6 among wild birds in the first quarter of 2018 in England and 69 individuals exposed to infected birds during these incidents. Five exposed individuals developed respiratory symptoms. However, no H5N6 infection was detected among those individuals with respiratory symptoms who underwent diagnostic testing, indicating that the human risk from this strain remains low. Abstract : Routine public health data was used to assess the risks to humans of exposures to H5N6 avian influenza among wild birds. No evidence of transmission of the virus from birds to humans was observed.